A Simplified Deformation Estimation Method for Anchor Piles of Sheet Pile Quay Walls under Kinematic Forces during Earthquakes - Miyashita, Kenichiro; Nagao, Takashi (Engineering, Technology & Applied Science Research, 2023)
In the seismic design of quay walls, it is necessary to evaluate the deformation of the walls during earthquakes as well as the safety of structural members. However, conventional seismic design methods for sheet pile quay walls cannot accurately determine the degree of deformation. One reason for this is that conventional methods do not consider kinematic forces acting on an anchor pile due to the deformation of the ground. This study proposes a simplified estimation method for anchor pile deformation under the influence of kinematic forces. The results of two-dimensional finite element analysis reveal that anchor pile deformation involves rotational and translational components caused by the kinematic forces, which the conventional methods do not consider. The deformation of the anchor pile caused by kinematic forces was 30%–40% of the total deformation at the pile head. It was clarified that unlike horizontally stratified ground, shear stress is generated in the ground before an earthquake resulting in the kinematic force acting on the anchor pile during the earthquake. Furthermore, a simplified method for estimating the deformation of the anchor pile under kinematic forces that uses one-dimensional seismic response analysis considering the predicted shear stress based on a theoretical equation is proposed. It was demonstrated that the proposed method accurately reproduces the anchor pile deformation.